Hatchability of Eggs and Larvae Survival of Common Carp (Cyprinus Carpio) Punten Strain On Exposure to Endosulfan Insecticide with Different Concentrations (Agrikan Jurnal Agribisnis Perikanan, 2022)
One type of organochlorine pesticide used by farmers is endosulfan. Excessive use of pesticides can cause environmental and water pollution and have an impact on the life of freshwater biota such as goldfish (Cyprinus carpio) Punten strain. The purpose of this study was to determine the value of LC50-168 hours of endosulfan insecticide on mortality of carp (Cyprinus carpio) eggs and to compare egg hatchability and survival of goldfish (Cyprinus carpio) larvae on exposure to endosulfan insecticides with different concentrations. This study used a completely randomized design (CRD) with 3 treatments and 1 control. Each treatment was repeated three times, namely P0 = 0 ppm (control), P1 (0.01 ppm), P2 (0.1 ppm), and P3 (1 ppm). Analysis of Variens (ANOVA) and DNMRT (Duncan New Multiple Range Test) were used to compare egg hatchability and larval survival at different concentrations of endosulfan insecticides. The results of the acute toxicity test (LC50-168 hours) of carp eggs were at a concentration of 0.6 ppm, there was a significant difference in hatchability of goldfish eggs (Cyprinus carpio) Punten strain exposed to endosulfan insecticide exposure with different concentration levels the higher the endosulfan concentration. used, the lower the hatchability of goldfish (Cyprinus carpio) eggs, and the survival rate of goldfish (Cyprinus carpio) larvae was different at various levels of endosulfan concentration. The higher the endosulfan concentration, the lower the survival rate of goldfish (Cyprinus carpio) larvae.
Keywords: Daya tetas; Ikan mas; Cyprinus carpio; Insektisida Endosulfan